2021
DOI: 10.3389/fpls.2021.625799
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Responses of Spanish Moss Tillandsia usneoides to Atmospheric Hg and Hormesis in This Species

Abstract: Hg is an environmental pollutant with severe biotoxicity. Epiphytic Tillandsia species, especially Spanish moss T. usneoides, are widely used as the bioindicator of Hg pollution. However, the effects of different Hg concentrations on Tillandsia have been rarely studied and the occurrence of hormesis in Tillandsia species has not been determined. In this study, T. usneoides was subjected to stress induced by 15 concentrations of gaseous Hg ranging from 0 to 1.8 μg m–3 through a misting system and then Hg conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Another species of Tillandsia, T. usneoides, showed a predominant biphasic hormetic response at 10 different atmospheric lead-Pb concentrations; the hormetic response was confirmed by the levels of malondialdehyde (MDA) and superoxide anion radical and the superoxide dismutase (SOD) activity after 6-12 h, as well as by GSH and metallothionein-MT content after 12 h [27]. SOD, GSH, and MT also showed a hormetic response in T. usneoides exposed to different mercury-Hg atmospheric concentrations [28].…”
Section: Potentially Toxic Elements and Eustressmentioning
confidence: 95%
“…Another species of Tillandsia, T. usneoides, showed a predominant biphasic hormetic response at 10 different atmospheric lead-Pb concentrations; the hormetic response was confirmed by the levels of malondialdehyde (MDA) and superoxide anion radical and the superoxide dismutase (SOD) activity after 6-12 h, as well as by GSH and metallothionein-MT content after 12 h [27]. SOD, GSH, and MT also showed a hormetic response in T. usneoides exposed to different mercury-Hg atmospheric concentrations [28].…”
Section: Potentially Toxic Elements and Eustressmentioning
confidence: 95%
“…It is also a microhabitat that is a shelter for various organisms including one species of jumping spider, various species of bats and also rat snakes. In Schreck et al (2019) and Sun et al (2021) stated that the ornamental plant has an effective function as a bioindicator of metallic contamination and an indicator of atmospheric contamination. In, Rini et al (2008) and Rindita et al (2015), atmospheric contamination can occur due to air pollution caused by vehicles which are the main source of producing carbon dioxide, nitrogen oxides and sulfur oxides.…”
mentioning
confidence: 99%
“…The MDA content at MRC was lower than MRRJ. In one study, T. usneoides was more resistant to membrane damage than A. fasciata (Giampaoli et al, 2021), while the aforementioned Hg exposure study revealed no significant difference in MDA concentrations with increasing Hg, indicating T. usneoides resistance to this metal (Sun et al, 2021a).…”
Section: Mda Content In Tillandsia Speciesmentioning
confidence: 97%
“…Moss, lichens and epiphyte plants are mostly employed for this purpose, as they obtain nutrients from the air by gaseous changes that occurs in their stomates and/or trichomes (Alves et al, 2008;Gioda et al, 2021;Zheng et al, 2017). Tillandsia species are excellent biomonitors in this context, obtaining their nutrients from the atmosphere and exhibiting high absorptive capacity (Sun et al, 2021a). Furthermore, as they are widely distributed in tropical areas, Tillandsia species are often chosen for atmospheric biomonitoring efforts in South America De La Cruz et al, 2021;Gioda et al, 2021;Piazzetta et al, 2019).…”
Section: Introductionmentioning
confidence: 99%